2021
DOI: 10.1007/s11618-021-01014-7
|View full text |Cite
|
Sign up to set email alerts
|

(Digitale) Elternzusammenarbeit in Kindertageseinrichtungen während der Corona-Pandemie. Digitalisierungsschub oder verpasste Chance?

Abstract: ZusammenfassungDie Schließung von Kindertageseinrichtungen (Kita) als Maßnahme zur Eindämmung des Corona-Virus stellte frühpädagogische Fachkräfte kurzfristig vor veränderte Tätigkeitsbedingungen und Möglichkeiten, den weiterhin bestehenden Bildungsauftrag umzusetzen. Die Zusammenarbeit mit Eltern, mit und ohne digitale Medien, spielt in dieser Hinsicht eine wichtige Rolle. Der Beitrag untersucht a) wie häufig und in welcher Form Fachkräfte die Elternzusammenarbeit in der Corona-Schließzeit umsetzten, b) welch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 53 publications
(68 reference statements)
0
5
0
1
Order By: Relevance
“…In general, preschools are ill-prepared for pandemics (Shope et al, 2017;Pramling Samuelsson et al, 2020). Many ECEC professionals lack knowledge and competencies in dealing with pandemics in professional practice, including adopting information and communication technologies (ICT) for educational purposes (Jones, 2020;Pramling Samuelsson et al, 2020;Tarrant and Nagasawa, 2020;Cohen et al, 2021). Langmeyer et al (2020) found that, even if family households are equipped with ICT, most children in Germany had little contact with their educators.…”
Section: The Covid-19 Pandemic and Professional-parent Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, preschools are ill-prepared for pandemics (Shope et al, 2017;Pramling Samuelsson et al, 2020). Many ECEC professionals lack knowledge and competencies in dealing with pandemics in professional practice, including adopting information and communication technologies (ICT) for educational purposes (Jones, 2020;Pramling Samuelsson et al, 2020;Tarrant and Nagasawa, 2020;Cohen et al, 2021). Langmeyer et al (2020) found that, even if family households are equipped with ICT, most children in Germany had little contact with their educators.…”
Section: The Covid-19 Pandemic and Professional-parent Collaborationmentioning
confidence: 99%
“…Langmeyer et al (2020) found that, even if family households are equipped with ICT, most children in Germany had little contact with their educators. However, Cohen et al (2021) found that 75% of professionals used ICT for contacting parents, though most of these contacts were sporadic. Institutional rules at the ECEC services, particularly in ECEC centers, have also affected professionals' relationships with parents, such as data protection or prohibition of usage of personal devices for contacting parents (Studienleitungen "Elementarpädagogik/Elementarbildung" an Österreichs Pädagogischen Hochschulen and Projektteam, 2020).…”
Section: The Covid-19 Pandemic and Professional-parent Collaborationmentioning
confidence: 99%
“…Mirroring findings from other countries (Dayal and Tiko, 2020;Tarrant and Nagasawa, 2020), our findings illustrate that many professionals are motivated to use ICT for creative and educational contact activities with children. Similarly, Cohen et al (2021) showed that attitudes toward using ICT have changed positively since the beginning of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…As the responses showed, this prohibition in ECEC centers was mostly justified by data protection requirements or guidelines regarding access to parents' contact information. Data protection and data security are traditionally given high priority in German institutions and, therefore, strongly influence the cooperation between ECEC professionals and families (Cohen et al, 2021). Research has shown that this issue is not specific to Germany; professionals in Austria have described similar challenges (Studienleitungen "Elementarpädagogik/Elementarbildung" an Österreichs Pädagogischen Hochschulen and Projektteam, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation